The Impact of School Principals' Managerial Skills and School Climate on Teacher Performance - Papilaya, Josef; Nanda, Fitri Agung (Journal for Lesson and Learning Studies, 2024)
Teacher performance is a key factor in supporting the success of the learning process in schools. However, a lack of attention to the managerial skills of school principals and the school climate often hampers efforts to improve teacher performance. This study aims to analyze the influence of school principals’ managerial skills and the school climate on teacher performance. A quantitative descriptive approach was employed, involving 80 school principals as the sample. Data were analyzed using the Chi-Square test and linearity test to examine the linear relationship between the independent variables (managerial skills and school climate) and the dependent variable (teacher performance). The results showed a simultaneous significance value of 0.000 (probability < 0.05), with an F-value of 2334.4, exceeding the F-table value of 3.115. These findings indicate that the managerial skills of school principals and the school climate significantly affect teacher performance. This study concludes that strong managerial skills and a conducive school climate can enhance teachers' motivation and performance, positively impacting the quality of teaching and learning.